Attitudes and preferences toward the adoption of voice-controlled intelligent personal assistants: Evidence from Croatia - Antun Biloš; Bruno Budimir; Borna Kraljević (Information Research: An International Electronic Journal)
Purpose. The primary goal of this paper was to explore the current level of voice-controlled intelligent personal assistant (IPA) adoption in a non-English speaking European country. This relatively novel technology exhibited immense growth in recent years, both on smartphones and as standalone devices with yet insufficiently explored usage patterns and implications associated with the internet of things (IoT) concept.